Faktor – Faktor Makro Ekonomi Yang Mempengaruhi Permintaan Uang Di Indonesia Periode 2015 – 2022 - Sucitra Ramadhoni Awalia; Lilis Karlina; Chasmira Ashara; Muhammad Maftuh Ihsan; Fitria Rahmah (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
The demand for money plays an important role for monetary policy authorities in determining appropriate policies to maintain economic stability. Money demand analysis is an analysis of the economic quantity needed to support the policies implemented by the government in the monetary sector. The aim of this research is to determine and analyze the influence of the Gross Domestic Product variables, exchange rate, interest rates and inflation, on the demand for money in Indonesia in 2015-2022. This research includes quantitative research with an associative approach. The data used is secondary data with quarterly time series data from 2015-2022 obtained from Bank Indonesia and the Central Statistics Agency (BPS). The research results show that there is a significant influence of GDP, exchange rates, interest rates and inflation on M1.